2023
DOI: 10.1002/anie.202213968
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between Acidic and Basic Surface Hydroxyls on Metal Oxides by Fluoride Substitution: A Case Study on Blue TiO2 from Laser Defect Engineering

Abstract: Both oxygen vacancies and surface hydroxyls play a crucial role in catalysis. Yet, their relationship is not often explored. Herein, we prepare two series of TiO 2 (rutile and P25) with increasing oxygen deficiency and Ti 3 + concentration by pulsed laser defect engineering in liquid (PUDEL), and selectively quantify the acidic and basic surface OH by fluoride substitution. As indicated by EPR spectroscopy, the laser-generated Ti 3 + exist near the surface of rutile, but appear to be deeper in the bulk for P25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 111 publications
(369 reference statements)
1
8
0
Order By: Relevance
“…The latter originates from Ti 3+ -sites in disordered STO phases, where pronounced site-to-site disorder leads to a broad distribution of g-values (g-strain). 40,42,43 Furthermore a six line spectrum with a hyperfine splitting of 237 MHz is observed, which matches very well with reported values for Mn 2+ (S = 5/2, I = 5/2) substituting Ti 4+ sites. 44 UV light exposure in the absence of MeOH only led to minimal changes of the EPR spectrum (see Fig.…”
Section: Epr Spectroscopysupporting
confidence: 90%
“…The latter originates from Ti 3+ -sites in disordered STO phases, where pronounced site-to-site disorder leads to a broad distribution of g-values (g-strain). 40,42,43 Furthermore a six line spectrum with a hyperfine splitting of 237 MHz is observed, which matches very well with reported values for Mn 2+ (S = 5/2, I = 5/2) substituting Ti 4+ sites. 44 UV light exposure in the absence of MeOH only led to minimal changes of the EPR spectrum (see Fig.…”
Section: Epr Spectroscopysupporting
confidence: 90%
“…Moreover, the XPS results (Table S5, ESI †) show that Ti(SO 4 ) 2 /TS-400 1C has the highest number of surface hydroxyl groups, which is attributed to the presence of oxygen vacancies accompanied by the unsaturated Ti 3+ species. 27 It can be confirmed that the variable valence of Ti species and the generation of Ti 3+ species increases the acidity of the Ti(SO 4 ) 2 /TS catalyst, while the transformation between Ti 4+ and Ti 3+ also promotes the redox cycle of the DME oxidation reaction.…”
mentioning
confidence: 86%
“…26 The presence of oxygen vacancies promotes the charge transfer between TiO 2 and Ti(SO 4 ) 2 , which may increase the electron density of the bridged oxygen and the proton affinity to form more –OH groups. 27 It has been reported that the structure of sulfate species significantly affects the acidic properties of the catalysts. From Fig.…”
mentioning
confidence: 99%
“…Photocatalytic performance heavily relies on the formation of reactive oxygen species, where the hydroxyl radical (•OH) and superoxide anion (•O 2 – ) play a major role . Surface hydroxyl (OH) has been proven to effectively promote the generation of reactive oxygen species by enhancing charge separation in previous reports as well as our work. , Various methods have been proposed for regulating OH, such as pulsed laser irradiation, hydrothermal treatment, and solvent-controlled synthesis . However, these methods required complex treatments or rigorous synthesis.…”
Section: Introductionmentioning
confidence: 96%